EKSPERIMENTASI TEKNIK LILIT PELEPAH PINANG PADA MEDIA TOPLES BEKAS SEBAGAI WADAH PENYIMPANAN DEKORATIF - Febriani Sri Cenli Senta; Anastasia Dalus; Arnesta Vigi Sempol; Yustina Makda Mia; Beatayu Trisna Saigon; Faleriani Asmin; Vincentius Mariano Dahas (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The utilization of inorganic waste such as plastic jars and organic waste such as areca palm fronds has not yet been optimized. This study aims to explore the wrapping technique using areca palm fronds as a covering material for used plastic jars in order to create storage containers with aesthetic and functional value. The method employed in this study is a formal experimental approach, which includes material preparation, softening the areca palm fronds, combing the fronds into string-like fibers, cutting the used jars to the required size, and applying the wrapping process. The results indicate that areca palm fronds possess a unique natural texture capable of transforming used plastic jars into decorative products with higher aesthetic appeal and economic value. These findings demonstrate that the combination of organic and inorganic waste materials can contribute to sustainable and value-added recycled products (Ayu, 2021; Sukarsih, 2020).